Legal Regulation of Financial Accounting and Audit as Legal Institute of Public Finance Law - Endrijaitis, Martynas (Teisė, 2018)
[only abstract in English; full article, abstract in Lithuanian] The article reveals that legal regulation of financial accounting and audit must be defined (and separated) as self-dependent, separated and no doubt very important legal institute of public finance law. There are concrete arguments disclosed validating the resolution to define this legal institute as self-dependent and very important legal institute of public finance law. As a consequence, the purpose of this article is to prove that legal regulation of financial accounting and audit is self-dependent legal institute of public finance law. The object of this article is disclosure of legal regulation of financial accounting and audit in the view of public finance law. Performed analysis of problematical questions discloses that legal regulation of financial accounting and audit shall be described as system of international, EU, national and local (adopted by entity) sources of law which has the characteristic for permanent development (renewal, addition) of legal norms. Consequently, the trend is observed that this system is liable to detailed legal regulation of specific legal relations of public finance. The article reveals that main features of basic concepts of law (positive law, legal realism, natural law) are identified in legal regulation of financial accounting and audit as, no doubt, this legal institution can be defined (and separated) as self-dependent, separated and very important legal institute of public finance law. Main features are clear creation of legal sources; formally described legal norms; the core of legal regulation - legal norms of legal behavior; system of legal norms; forcible nature; reflexion and dynamics of legal norms; efficiency of legal norms coming from legal realism (development of case-court practice); verification of the mainstream of value-system by which concrete legal norms must follow (verification of operation of generally accepted financial accounting principles). This scientific research reveals that articles main legal arguments, why legal regulation of financial accounting and audit must be defined (and separated) as self-dependent, separated and very important legal institute of public finance law, allow to identify main features of legal institute of public finance law: 1) legal regulation of financial accounting and audit regulates specific social relations; 2) these legal norms have social importance; 3) there are concrete, special, self-dependent sources of law applied only for this legal institution; 4) the main legal regulation method is dispositive method, although there can be found imperative method.